2003
DOI: 10.1099/vir.0.19546-0
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus core protein VII contains distinct sequences that mediate targeting to the nucleus and nucleolus, and colocalization with human chromosomes

Abstract: During adenovirus infection, following capsid dissociation, core protein VII enters the host cell nucleus complexed with adenovirus DNA. In order to determine whether protein VII may have an active role in this nuclear import, regions of the preVII gene were amplified by PCR, and further oligonucleotide mutants were designed with site-directed mutation of codons for the basic amino acids arginine and lysine. Fragments were cloned into a mammalian expression plasmid to express the peptides as N-terminal fusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
52
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 29 publications
7
52
1
Order By: Relevance
“…The strong DNA binding of protein VII and the timing of its nuclear import after infection make it a good candidate for facilitating the nuclear import of the adenovirus genome (5,16,30,47). Recent studies by Lee et al (30) have shown that green fluorescent protein (GFP) fusions containing protein VII or fragments thereof accumulate in the nucleus in transfected cells.…”
mentioning
confidence: 99%
“…The strong DNA binding of protein VII and the timing of its nuclear import after infection make it a good candidate for facilitating the nuclear import of the adenovirus genome (5,16,30,47). Recent studies by Lee et al (30) have shown that green fluorescent protein (GFP) fusions containing protein VII or fragments thereof accumulate in the nucleus in transfected cells.…”
mentioning
confidence: 99%
“…Several other Ad proteins have been shown to localize to nucleoli, including IVa2 (29), the viral core proteins V (30, 31), Mu (26), and protein VII (25). The Ad E4orf4 protein is also targeted to nucleoli (33).…”
Section: Discussionmentioning
confidence: 99%
“…Recent intracellular localization and functional studies of Mu, pV, and pVII were performed with carboxy terminal fusion of EGFP to the native proteins (Lee et al, 2003(Lee et al, , 2004Matthews, 2001). Our attention was drawn to three established observations from these reports:…”
Section: Discussionmentioning
confidence: 99%
“…Protein VII (pVII) is the major core protein contributing over 800 copies per virion (Lehmberg et al, 1999). Expressed as a 174 amino acid precursor from which a 24 amino acid N-terminus is cleaved (Sung et al, 1983), its functional and sequence homology to histone H3 (Cai and Weber, 1993;Lee et al, 2003) indicates that pVII acts as a histone-like center around which viral DNA is wrapped to form nucleosome structures (Chatterjee et al, 1986;Mirza and Weber, 1982). Protein V (pV) is speculated to serve as a bridge between the genome core and the capsid through association with proteins Mu, VI, and VII as well as the viral DNA (Chatterjee et al, 1985;Matthews and Russell, 1998;Vayda and Flint, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation